Visual Aesthetics Semiotics Roland Barthes Photography Journalistic Works Phenomenal World - Prasetyo, Martinus Eko; Imamul Masyhudi (IMAGIONARY, 2024)
Documentary photography as a medium of conveying information and documentation can document reality and tell important stories with integrity and honesty. Where journalistic photography will continue to be a powerful tool in reporting the truth and influencing social change, giving us a window into a wider and more diverse world. This research visually analyzes the phenomenal works of world photography from the aesthetic side with Roland Barthes' semiotic approach. It tells that aesthetically the photograph is an embodiment of visual beauty immortalized by the photographer not only by chance in capturing a moment that once existed. This research is conducted qualitatively descriptively according to Bogdan and Guba and proves that the science of photography does not only rely on luck but needs to understand how to photograph, the concept of visual framing in one frame that can be accepted by the general public as a conveyance of messages, information, and impressions from a photograph itself based on photographic theories.